2017
DOI: 10.1111/adb.12495
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol reduces ethanol consumption, motivation and relapse in mice

Abstract: This study evaluated the effects of cannabidiol (CBD) on ethanol reinforcement, motivation and relapse in C57BL/6 J mice. The effects of CBD (60 mg/kg, i.p.) on blood ethanol concentration, hypothermia and handling-induced convulsions associated to acute ethanol administration were evaluated. The two-bottle choice paradigm was performed to assess the effects of CBD (30, 60 and 120 mg/kg/day, i.p.) on ethanol intake and preference. In addition, an oral ethanol self-administration experiment was carried out to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
125
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(141 citation statements)
references
References 50 publications
(66 reference statements)
15
125
0
1
Order By: Relevance
“…There is mounting evidence that the endogenous cannabinoid (eCB) system is involved in motivation for rewards, including modulating the rewarding effects of drugs . In relation to nicotine dependence, cannabinoid receptor 1 (CB1R) antagonists, such as rimonabant, decrease nicotine conditioned place preference and self‐administration in pre‐clinical models of addiction .…”
Section: Introductionmentioning
confidence: 99%
“…There is mounting evidence that the endogenous cannabinoid (eCB) system is involved in motivation for rewards, including modulating the rewarding effects of drugs . In relation to nicotine dependence, cannabinoid receptor 1 (CB1R) antagonists, such as rimonabant, decrease nicotine conditioned place preference and self‐administration in pre‐clinical models of addiction .…”
Section: Introductionmentioning
confidence: 99%
“…Effective pharmacological targets for the treatment of drug abuse must diminish drug craving while leaving cognitive functions intact. Cannabidiol (CBD) is a compound of the herb Cannabis sativa that lacks the psychotomimetic and reinforcing properties . In the CNS, CBD has neuroprotective, antioxidative, and anti‐inflammatory properties .…”
Section: Introductionmentioning
confidence: 99%
“…In this previous study, we showed that animals treated with CBD (20 mg/kg) during the acquisition phase of cocaine operant taking extinguished seeking behavior in a similar extent than control mice. Similarly, CBD (60 mg/kg) did not facilitate extinction learning of ethanol taking behavior in rats (Viudez-Martínez et al, 2018). Another study using heroin also described that CBD (10, 20 mg/kg) did not affect lever pressing during extinction training (Ren et al, 2009).…”
Section: Discussionmentioning
confidence: 95%
“…Other works hinted at a possible participation of CB1 receptors in the protective effects of CBD in drug selfadministration studies. Striatal CB1 mRNA expression was found reduced following a CBD treatment with drug seeking attenuating effects (Ren et al, 2009;Viudez-Martínez et al, 2018). The effects of AM4113 on CBD-induced changes during extinction learning indicates that the expression of these effects are modulated by CB1 cannabinoids receptors on reinstatement conditions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation